: 1 - ()

:

: 1540


2.4.2.

 

, .

, 2 (. . 1).

. (23)

:

m1(za + zg) = m2(zb - zf) 蠠 (za + zg) = zb - zf, (24)

m1 za zg, m2 zf zd.

; ; ; ; , (25)

(23) (24) :

; (26)

m (a + 1) = g - b = g(1j). (27)

(26)

. (28)

(27) (28),

. (29)

2zb > zf , j < 1. ( ³ 2) j < .

[2, 8, 9]: ; Q, PÎ Z , (30)

C , Z .

(30) , .1, 1 2, 3 4.

(30) , za zb [1]. z zb , Q P [9], [10], (30):

; q Î N, (31)

N .

(d)g (d)f l [1]. (l (d)g) (l (d)f ) 0,5m. d m (., . 4)

2 > 4 :

,

ha* ( 13755-81 ha* = 1).

2

> 4, (32)

< 4. (33)

1.

, 2, 1 zg = zf m = 1.

(23) , b = 1,

. .

. (34)

:

(za + 2zg) = zb. (35)

,

; (36)

a + 2 = g. (37)

(36) (37)

. (38)

(38) , 1

> 2. za , zg zb , IV II (. . 1).

1 (30) (31), zg = zf :

. (39)

:

. (40)

3 (. . 1) (), b h a:

. (41)

:

m1(za zg) = m2(zb - zf) 蠠 (za zg) = zb - zf. (42)

(23), (41)

(42):

; (43)

m (a 1) = g - b = g(1j). (44)

(43)

. (45)

(44) (45),

. (46)

3 za > zg zb > zf , a > 1 j < 1. (46) j ¹ 1. , ( ³ 2) a > 2 j <.

(30), (31)

zg > zf (47)

zf > zg. (48)

4 , h . 3, h, b:

. (49)

:

m1(za + zg) = m2(zb + zf) 蠠 (za + zg) = zb + zf. (50)

(23) (49), (50):

; (51)

. (52)

4 (30) (31)

zg > zf (53)

zf > zg . (54)

 

| |